A CRITICAL READING: CONTRADICTORY PERSPECTIVES ON PATRIARCHY AS SEEN IN THE FEMALE CHARACTERS OF MARY E. WALKINS FREEMAN’S “THE REVOLT OF ‘MOTHER’ ” - Nandy Intan Kurnia (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
Many students of English Language and Literature study program analyze “The Revolt of ‘Mother’ “, which is a short story written by Mary E. Walkins Freeman, by using a feminist approach. Most of them are trying to focus their attention to its’ female major character, named Sarah Penn. She is seen as a strong woman who has a courage to speak up her mind and break the patriarchal system. However, it is also important to question the point of view of the other female character in Freeman’s short story. A critical reading on this work can give new insights of the women perspectives on patriarchy. Therefore, this paper explores the contrast of women perspectives in relation to the patriarchal system as reflected in one of Freeman’s short stories.Keywords: A critical reading, patriarchal system, women’s contradictory perspectives.